1999
DOI: 10.1093/emboj/18.19.5399
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the exosome in rRNA, snoRNA and snRNA synthesis

Abstract: C.Allmang and J.Kufel contributed equally to this workThe yeast nuclear exosome contains multiple 3Ј→5Ј exoribonucleases, raising the question of why so many activities are present in the complex. All components are required during the 3Ј processing of the 5.8S rRNA, together with the putative RNA helicase Dob1p/Mtr4p. During this processing three distinct steps can be resolved, and hand-over between different exonucleases appears to occur at least twice. 3Ј processing of snoRNAs (small nucleolar RNAs) that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

41
652
2
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(699 citation statements)
references
References 48 publications
41
652
2
4
Order By: Relevance
“…19 The exosome is the nucleolus-associated machinery involved in many aspects of RNA quality control and surveillance 31 as well as in rRNA processing. 32 In an Y2H screen, TTRAP was found to bind to a regulatory subunit of yeast analogue of the human exosome (BIND database). It will be interesting to study whether nucleolar cavities are sites for exosome activity and TTRAP might contribute to regulate exosome function.…”
Section: Discussionmentioning
confidence: 99%
“…19 The exosome is the nucleolus-associated machinery involved in many aspects of RNA quality control and surveillance 31 as well as in rRNA processing. 32 In an Y2H screen, TTRAP was found to bind to a regulatory subunit of yeast analogue of the human exosome (BIND database). It will be interesting to study whether nucleolar cavities are sites for exosome activity and TTRAP might contribute to regulate exosome function.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest explanation would be that the absence of any of the subunits causes a failure to assemble the whole complex or inactivates it (1). However, it was shown that a yeast strain lacking two exosome subunits showed stronger phenotypes than either single mutant (16), which suggests that the absence of one component does not inactivate the entire complex. In the present work we have studied systematically the effect that the depletion of any of the components of the T. brucei exosome has on the stability of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…All yeast exosome components are essential for viability, with the exception of Rrp6p, and depletion of each of them yields broadly similar defects in RNA processing (16). Likewise, depletion of all exosome component homologues in T. brucei, with the possible exception of the Csl4p homologue, results in cell death and in very similar defects in 5.8 S rRNA processing (8).…”
mentioning
confidence: 99%
“…The yeast polycistronic snoRNA precursors are processed by Rnt1p, a homologue of bacterial RNase III (13). The liberated 5Ј and 3Ј ends are further processed by 5Ј 3 3Ј-exonucleases Rat1p and Xrn1p, and the 3Ј 3 5Ј-exosome (including Rrp6p) (14,15).Trypanosomatids are unicellular protozoan parasites that diverged very early from their eukaryotic lineage. These organisms possess unique RNA processing mechanisms such as pre-mRNA trans-splicing and RNA editing (16,17).…”
mentioning
confidence: 99%
“…The yeast polycistronic snoRNA precursors are processed by Rnt1p, a homologue of bacterial RNase III (13). The liberated 5Ј and 3Ј ends are further processed by 5Ј 3 3Ј-exonucleases Rat1p and Xrn1p, and the 3Ј 3 5Ј-exosome (including Rrp6p) (14,15).…”
mentioning
confidence: 99%